Acute Temporal Tendinitis After Dental Extraction: A Valuable Lesson - Nor Azura Ahmad Tarmidzi; Mohamed Hisham Mohamed Jali @ Yunos; Faezah Rokhani; Mohamad Nazmi Nisar Ahmad (Universiti Putra Malaysia, 2026)
Tier 2- Indexed by SCOPUS/ MyCite